A COMPARATIVE STUDY OF TERBINAFINE ETHOSOMAL FORMULATIONS: A NOVEL APPROACH - R., Narayana Charyulu; Satveek, Mehta; M., Harish N.; Patil, Amit B. (Journal of Health and Allied Sciences NU, 2013)
The present research work aimed at the impact of reduced vesicular size on the characteristics of ethosomes by comparing with the regular vesicular size of ethosomes as topical drug delivery vehicle to achieve optimal localized drug concentration and reduced dose frequency of the Terbinafine hydrochloride (TH), an antifungal drug. Oral use of TH contraindicated resulting from sever side effect, thus topical administration is recommended. Commercially available TH creams, lotions and sprays, have limitation of relatively short residual period at target site. The entrapment of drug in vesicles improves localization, solubility and availability of drug at the site; resulting in reduction of the dose. Ethosomes containing drug were prepared by employing higher concentration of alcohol in the form of hydroalcoholic or hydroglycolic phospholipid. Sonicated and unsonicated ethosomes were investigated for shape, particle size, and entrapment efficiency. Electronic microscope investigation not only revealed, vital evidence for presence of phospholipid vesicles in TH ethosomal systems but also displayed greater uniformity in size and shape of sonicated ethosomes than unsonicated ethosomes. Furthermore, the Comparative investigation was carried out for ex vivo skin permeation, ex vivo drug release and entrapment efficiency studies. Drug release followed zero order release rate kinetics. Drug accumulation study showed more than 19.01 % of drug was deposited into skin by sonicated ethosomal formulation as compared to 2.57 % by unsonicated ethosomal formulation. Sonicated and unsonicated ethosomes were found stable at refrigeration and room temperature conditions during stability studies. Drug accumulation studies in deep skin strata was found to be comparatively greater in sonicated ethosomes, which indicates higher localized drug and that in turn reduces dose frequency.
Keywords: Sonicated Ethosomes; unsonicated ethosomes; Terbinafine hydrochloride; ex vivo characterization